CRISPR-CasRx Targeting LncRNA LINC00341 Inhibits Tumor Cell Growth in vitro and in vivo - Li, Chunjing; Cao, Yu; Zhang, Li; Li, Jierong; Wang, Jianfeng; Zhou, Yanfen; Wei, Huiling; Guo, Mingjuan; Liu, Liang; Liu, Chunxiao; Zhang, Shilin; Liu, Guoqing (Frontiers in Molecular Biosciences, 2021)
The CRISPR-CasRx technology provides a new and powerful approach to study cellular RNAs in human cancers. The current study is to investigate the expression pattern and biological function of long non-coding RNA 341 (LINC00341) in bladder cancer using CRISPR-CasRx. The expression levels of LINC00341 were determined using Real-Time qPCR in tumor tissues and paired normal tissues. Human bladder cancer T24 and 5637 cell lines were transiently transfected with sgRNA targeting LINC00341 or sgRNA negative control. Cell proliferation, apoptosis and migration were determined using CCK-8 assay, ELISA assay and wound healing assay, respectively. Cell proliferation was also confirmed by tumorigenicity assay in nude mice. Western blot assay was used to detect expression changes of p21, Bax and E-cadherin after sgRNA transfection. The results demonstrated that LINC00341 was overexpressed in bladder cancer tissues compared with matched normal tissues. LINC00341 expression levels were higher in high grade tumors than those in low grade tumors. LINC00341 expression levels were higher in invasive tumors than in non-invasive tumors. Inhibition of cell proliferation (both in vitro and in vivo), increased apoptosis, and decreased motility were observed in LINC00341 sgRNA-transfected T24 and 5637 cell lines. Furthermore, silencing of LINC00341 increased p21, Bax and E-cadherin expression and knockdown these genes can eliminate the phenotypic changes induced by sgRNA targeting LINC00341. These findings suggest that LINC00341 plays a oncogenic role in human bladder cancer.